Food processing the brewing of beer - Satterlee, Lowell D.; Pennsylvania State University.|bDept. of Food Science; Educational Communications, inc.; Pennsylvania State University.|bMedia Sales (University Park Penn State Media Sales New York distributed by Insight Media, 2006)
How beer is brewed is illustrated by a small brewery in Pennsylvania
Host: Lowell D. Satterlee
Keywords: Beer; Brewing; Beer industry; Documentary films